Alma and how she got her name - Martinez-Neal, Juana (Somerville, Massachusetts : Candlewick Press, 2018)
When Alma Sofia Esperanza José Pura Candela asks her father why she has so many names, she hears the story of her name and learns about her grandparents.
Keywords: Families -- Fiction; Names, Personal -- Fiction; Family -- Fiction; Personal names -- Fiction